Propensity-Adjusted Comparative Analysis of Radial Versus Femoral Access for Neurointerventional Treatments. Issue 6 (13th February 2021) - Catapano, Joshua S; Ducruet, Andrew F; Nguyen, Candice L; Majmundar, Neil; Wilkinson, D Andrew; Cole, Tyler S; Baranoski, Jacob F; Cavalcanti, Daniel D; Fredrickson, Vance L; Srinivasan, Visish M; Rutledge, Caleb; Lawton, Michael T; et al.
Abstract: BACKGROUND: Transradial artery (TRA) catheterization for neuroendovascular procedures is associated with a lower risk of complications than transfemoral artery (TFA) procedures. However, the majority of literature on TRA access pertains to diagnostic procedures rather than interventional treatments. OBJECTIVE: To compare TRA and TFA approaches for cerebrovascular interventions. METHODS: All patients with an endovascular intervention performed at a single center from October 1, 2018 to December 31, 2019 were retrospectively analyzed. Patients were grouped into 2 cohorts on the basis of whether TRA or TFA access was used. Outcomes included complications, fluoroscopy times, and total contrast administered. RESULTS: A total 579 interventional treatments were performed during the 15-mo study period. TFA procedures (n = 417) were associated with a significantly higher complication rate than TRA (n = 162) procedures (43 cases [10%] vs 5 cases [3%]; P = .008). After excluding patients who underwent thrombectomy and performing a propensity adjustment (including age, sex, pathology, procedure, sheath size, and catheter size), TRA catheterization was associated with decreased odds of a complication (odds ratio, 0.25; 95% CI 0.085-0.72; P = .01), but no significant difference in the amount of contrast administered (6.7-mL increase; 95% CI, −7.2 to 20.6; P = .34) or duration of fluoroscopy (2.1-min increase; 95% CI, −2.5 to 6.7; P = .37) compared with TFA catheterization. CONCLUSION: Neurointerventional procedures and treatments for a variety of pathologies can be performed successfully using the TRA approach, which is associated with a lower risk of complications and no difference in fluoroscopy duration compared with the TFA approach.